Understanding Japanese society - Hendry, Joy. (London; New York : Routledge, 1995)
Sources of Japanese identity. The house and family system. Socialisation and classification. Community and neighbourhood. Status and stratification in the wider world...
Keywords: Japan; Social conditions; Japan -- Social conditions